2015
DOI: 10.1007/s00244-015-0165-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Predator Cues on Responses to Silver Nanoparticles in Daphnia carinata

Abstract: The past decades have witnessed a boom in nanotechnology that has led to increasing production and application of silver nanoparticles (AgNPs) in the textile industry due to their antimicrobial properties. Increase in the manufacture and use of NPs inevitably has resulted in their increased release into aquatic environments resulting in the exposure of organisms living in these environments. Recently, the risk of exposure to NPs and the potential interaction with biological systems has received increasing atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 88 publications
(121 reference statements)
1
11
2
Order By: Relevance
“…Many other studies have found that very low concentrations of silver (0.05–6 µg/L) decrease daphnid reproduction , and some of these studies report decreased reproduction at concentrations that do not cause significant mortality or have any observable effect on zooplankton growth , similar to the present results for the highest food rations studied.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Many other studies have found that very low concentrations of silver (0.05–6 µg/L) decrease daphnid reproduction , and some of these studies report decreased reproduction at concentrations that do not cause significant mortality or have any observable effect on zooplankton growth , similar to the present results for the highest food rations studied.…”
Section: Discussionsupporting
confidence: 90%
“…Most studies have found that Ag ions (Agþ) are toxic at parts per billion concentrations to Daphnia [13][14][15][16][17][18][19][20][21][22]. Also, AgNPs are toxic at these low concentrations [15,21,[23][24][25][26][27], and there is agreement in the literature that Agþ is more toxic at equimolar Ag concentrations than AgNPs (see Ivask et al [28] for a review of the literature). Longer (chronic) experiments have observed reductions in growth and/or reproduction of Daphnia exposed to Ag, as both Agþ [29] and AgNPs [21,[30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is estimated that the production and usage of AgNPs could be over 1, 000 tons in 2015 (Stensberg et al, 2011). The increasing application of AgNPs raises concerns about their potential adverse effects to human and the environment (Cañas-Carrell et al, 2013Tang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%